Decision Making In Determining CV. Sinar Siantar With The TOPSIS Technique - Indra Riyana Rahadjeng (IJISTECH (International Journal of Information System and Technology), 2020)
This research aims to build a decision support system in ranking the routes that are passed by public transportation. Pematangsiantar (often abbreviated as Siantar only) is one of the cities in North Sumatra Province, and the second-largest city in the province after Medan. Due to the strategic location of Pematangsiantar, the Trans Sumatra toll road was crossed. The city has an area of 79.97 km2 and a population of 240,787 people (2010). Public transportation is one of the transportation used by the community together and pays the fare. So far, public transportation is part of urban transportation which has an important role in people's lives. However, this problem is still hampered by problems of the route that must be traversed by public transportation, especially Sinar Siantar. Decision support systems are interactive systems that support decisions in decision interpretation with alternatives obtained from the tabulation of data, information and model planning. In this research, the method used is Technique For Order Preference By Similarity To Ideal Solution (TOPSIS). The TOPSIS method is based on the concept that the best alternative chosen has not only the shortest distance from the positive ideal solution but also has the farthest distance from the negative ideal solution. The TOPSIS method has several advantages, including simple and easy to understand concepts, efficient computing, and the ability to measure the relative performance of alternatives in simple mathematical decision making. Based on the calculation, the value of the V3 process, which has the highest value is obtained, so that this route is the best alternative through the CV. Sinar Siantar is the alternative route to A3, namely Jalan Jawa, because the alternative criteria best meet all the other alternatives. This decision support system is expected to assist in determining public transport routes to become more efficient so that the result is the determination of public transport routes.